The Efforts in Improving the Education Quality by School Principal at Vocational High School Muhammadiyah 7 Gondanglegi Malang - Abdulloh, Abdulloh; Muhtarom, Muhtarom; Mahdali, Fitriyah; Rahmani, Ashila (Bulletin of Science Education, 2022)
The focus of this research was emphasized on the quality of education at Vocational High Schools (SMK) Muhammadiyah 7 Gondanglegi, which is about the principal's efforts to improve the quality of education. There were several arguments that form the basis of this research. Firstly, this school is included one of the leading Vocational High Schools (SMK) in Malang Regency. Secondly, the school has issuing high quality graduates (outputs) where these graduates are now widely scattered in several colleges. The article aimed to analyze the quality of education at SMK Muhammadiyah 7 Gondanglegi, the principal's efforts in improving the quality of education and the principal's strategy in barriers to Improving the quality of education. The method used descriptive qualitative. The collecting data used documentation and interviews. The result showed that the principal's efforts to improve the quality of education which is done in many ways. The obstacles faced by school principals as well solutions or policies in improving the quality of education. The success of the principal in improving the quality of education, in this case the researcher reveals the success this by describing the achievements and reputations that were obtained and held by the SMK Muhammadiyah 07 Gondanglegi. Keywords: Education Quality, Improving Education Quality, Principal Quality